Monitoring the agri-food system in Myanmar: Agricultural input retailers – March 2021 survey round - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
To understand the effects of recent disruptions on Myanmar’s agricultural input sector, a telephone survey of input retailers was conducted in March 2021. Key findings: The majority of input retailers report declines in sales of all types of inputs compared to a year ago. Uncertainty about crop output prices and difficulties in accessing markets are reported as the main drivers of lower input purchases.; Fertilizer prices have risen between 10 and 20 percent compared to a year ago. With prices expected to rise substantially in the coming months due to shipping and transportation cost increases, retailers anticipate reductions in fertilizer purchases.; As is the case for commodity traders, input retailers are switching to cash purchases in place of inter-bank transfers for obtaining their inventory due to limited banking services.; Two-thirds of retailers have made credit available to customers, and 88 percent of those who have done so have experienced late repayments from farmers. Even though most input retailers expect eventual repayment, 30 percent plan to reduce the credit they will extend to farmers for the coming season.; The combination of uncertain crop prices, higher costs to access markets, financial market disruptions, and expected increases in input prices all point to lower farm investment in production inputs for the coming monsoon season. Recommended actions: The restoration of inter-bank transfer services will reduce transactions costs for input retailers.; Imports of fertilizer and agro-inputs through the ports need to be expedited. Similarly, restrictions on transportation must be lifted to avoid late delivery of inputs to farmers for the monsoon season.; Temporary measures to offset expected fertilizer price increases and to avoid reductions in fertilizer use by smallholder farmers in the coming monsoon season should be considered.